An industrial control loop decoupler for process control applications. (June 2022) - Hägglund, Tore; Shinde, Sumit; Theorin, Alfred; Thomsen, Ulf
Abstract: The paper describes a simple and efficient control loop decoupler for TITO (two inputs, two outputs) control systems. The inverted decoupling approach is used, and the feedforward filters are just static gains. The feedforward gains are determined in two ways, from a static analysis and from optimization. By investigating several cases found in literature, it is found that the two sets of feedforward gains are very close. The control loop decoupler is implemented in an industrial DCS system and simulation experiments as well as laboratory tests show that a significant reduction of the coupling is accomplished. Automatic tuning of the feedforward gains is derived and implemented in the system as well. Highlights: A PID control loop decoupler is presented. It is based on inverted decoupling using static feedforward. Design methods and automatic tuning procedures for the feedforward gains are presented. A significant reduction of the coupling for several cases found in literature is obtained. The decoupler is implemented in an industrial DCS system.